Electrically reversible cracks in an intermetallic film controlled by an electric field - Z. Q. Liu (Nature Portfolio, 2018)
Electric-field-induced cracks are generally detrimental to functionality of ferroelectric ceramics. Liu et al. use an intermetallic alloy and ferroelectric oxide junction to mediate the reversible formation of cracks at nanoscales, resulting in colossal electroresistance modulation for memory applications.